Manajemen Kepala Sekolah dalam Menumbuhkan Kompetensi Sosial di Madrasah Ibtidaiyah Muhammadiyah 10 Karang Anyar Rejang Lebong - Murniyanto Murniyanto (Institut Agama Islam Negeri (IAIN) Curup, 2020)
To create teachers with good social competence, the role of a school principal provides example. The success of the principal can be seen from his efforts to motivate the teacher’s socil competence. Need to carry out several policies including planning, organizing, implementing, and monitoring. Of course many obstacles faced by a school principal. The next most basic obstacle is to unite differences of opinion between the teachers. In the efforts of the headmaster so that the relationship of social competence among teachers can run according to his expectations, the headmaster of the MIM 10 implements a reward and puinishment system for all teachers